Colchicine, COVID‐19 and hematological parameters: A meta‐analysis. Issue 12 (28th October 2021) - Sarwar, Musharraf; Ali, Zahid; Fatima, Mahnoor; Sarfraz, Zouina; Sarfraz, Azza; Cherrez‐Ojeda, Ivan
Abstract: Introduction: Colchicine has the potential in reducing patient morbidity and mortality in COVID‐19 infection owing to its anti‐inflammatory properties. This study aims to determine the efficacy of colchicine in optimizing inflammatory hematological biomarker levels among COVID‐19 patients. Methods: In accordance to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 2020 statement guidelines, a systematic search was conducted using the following keywords: Colchicine, covid*, SARS‐CoV‐2, anti‐inflammatory, trials, clinical, hematological, laboratory. Databases were searched from December 2019 until August 26, 2021: MEDLINE/PubMed, Web of Science, Cochrane, Scopus, and EMBASE. Other sources were located through ClinicalTrials.Gov, manually searching SAGE, Science Direct, Elsevier, and Google Scholar. The meta‐analysis was conducted using Review Manager 5.4. Results: In total, six studies were included, of which four reported c‐reactive protein (CRP) standardized mean reductions in the colchicine group (N = 165) as opposed to the control (N = 252; SMD = −0.49, p < 0.001). On noting lactate dehydrogenase (LDH) values post treatment, the colchicine group (N = 204) showed significant reductions at the end of treatment compared to control (N = 290; SMD = −0.85, p < 0.001). Finally, the D‐dimer values in colchicine groups (N = 129) compared to control (N = 216) also documented a negative effect size (SMD = −0.9, p < 0.001). Conclusion: Colchicine has efficacy in reducing inflammatory biomarkers observed in moderate‐to‐severe COVID‐19 patients. It may be worthwhile to consider monitoring the clinical and laboratory parameters of patients in further trials to consider colchicine as a strong candidate for an adjunct to COVID‐19 treatment. Abstract : Colchicine, and the myriad of other drugs that are being tested for COVID‐19 can be better documented by inflammatory hematological biomarkers during clinical trials and testing.